Występowanie zjawiska pracoholizmu wśród pielęgniarek. Badania wstępne: The occurrence of workaholism among nurses. Preliminary research - Stychno, Ewa; Suska, Lidia (Management and Administration Journal, 2021)
Workaholism is the most socially accepted addiction in modern society. The aim of study was to investigate the workaholism among professional nurses, depending on age, education, work experience, number of children, and place of employment. The study was conducted in 2012. Robinson's WART scale in its polish adaptation by Wojdyło was used in the study to measure the addiction percentage. The study results showed that 18.69% of nurses are workaholics. High absorption with work is most common between people between 35-45 years of age, displaying the need of achieving an appropriate professional position and its prestige. Nurses with work experience of 20 or more years represent higher commitment to their profession. Persons with children have are more susceptible to becoming workaholic. Nurses working on preservative branches are more susceptible to the appearance of workaholism than those working on children and treatment wards. Above dissertations are inducing more distant exploration of the workaholism phenomenomin the occupational group of nurses through the prism of other variables.